Postcolonial narrative and the work of mourning : J.M. Coetzee, Wilson Harris, and Toni Morrison - Durrant, Sam, 1970- (Albany : State University of New York Press, 2004)
"Sam Durrant's book compares the ways in which the novels of J.M. Coetzee, Wilson Harris, and Toni Morrison memorialize the traumatic histories of racial oppression that continue to haunt our postcolonial era. The works examined bear witness to the colonialization of the New World, U.S. slavery, and South African apartheid, histories founded on a violent denial of the humanity of the other that had traumatic consequences for both perpetrators and victims. Working at the borders of psychoanalysis and deconstruction, and drawing inspiration from recent work on the Holocaust, Durrant rethinks Freud's opposition between mourning and melancholia at the level of the collective and rearticulates the postcolonial project and an inconsolable labor of remembrance."--Jacket
Specters of colonialism -- Speechless before Apartheid: J.M. Coetzee's inconsolable works of mourning -- Rites of communion: Wilson Harris's hosting of history -- Keeping it in the family: passing on racial memory in the novels of Toni Morrison -- Some kind of community.
Based on the author's thesis (Ph. D.)--Queen's University, Ontario.
Includes bibliographical references (pages 129-137) and index.
Print version record.
JSTOR
Keywords: Coetzee, J. M., -- 1940- -- Criticism and interpretation; Morrison, Toni -- Criticism and interpretation; Harris, Wilson -- Criticism and interpretation; Coetzee, J. M., -- 1940- -- Critique et interprétation.; Morrison, Toni -- Critique et interprétation.; Harris, Wilson -- Critique et interprétation.; Morrison, Toni -- 1931-2019 -- Crítica e interpretación; Coetzee, J. M., -- 1940-; Harris, Wilson; Morrison, Toni; Morrison, Toni; Coetzee, John M; Harris, Wilson; Narration (Rhetoric) -- History -- 20th century; African Americans in literature; South Africa -- In literature; Postcolonialism in literature; Apartheid in literature; Guyana -- In literature; Slavery in literature; Black people in literature; Grief in literature; Narration (Rhetoric); Noirs américains dans la littérature.; Postcolonialisme dans la littérature.; Apartheid dans la littérature.; Esclavage dans la littérature.; Personnes noires dans la littérature.; Chagrin dans la littérature.; Narration; Afrique du Sud dans la littérature.; Guyana dans la littérature.; Narration -- Histoire -- 20e siècle.; Guyana -- Dans la littérature.; LITERARY CRITICISM -- American -- General; African Americans in literature; Apartheid in literature; Black people in literature; Grief in literature; Literature; Narration (Rhetoric); Postcolonialism in literature; Slavery in literature; Guyana; South Africa; Dekonstruktion; Postkoloniale Literatur; Postkolonialismus; Rassenkonflikt; Trauma; Psychoanalyse; Englisch; 1900-1999; History; Criticism, interpretation, etc